2010
DOI: 10.1016/j.jconrel.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of synthetic Low Density Lipoprotein by leukemic stem cells — a potential stem cell targeted drug delivery strategy

Abstract: Chronic myeloid leukemia (CML) stem/progenitor cells, which over-express Bcr-Abl, respond to imatinib by a reversible block in proliferation without significant apoptosis. As a result, patients are unlikely to be cured owing to the persistence of leukemic quiescent stem cells (QSC) capable of initiating relapse. Previously, we have reported that intracellular levels of imatinib in primary primitive CML cells (CD34 + 38 lo/-), are significantly lower than in CML progenitor cells (total CD34 + ) and leukemic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…For example, there have been many successful studies using LDL-like nanoparticles for targeted drug delivery to cancer cells. 7,13,[30][31][32][33][34][35] LDL nanoparticles containing lipophilic gadolinium complexes such as Gd-AAZTAC17 are also utilized as MRI probes for tumor cells in vitro and in vivo. 9 Similarly, many HDL nanoparticles have also been developed as drug or gene delivery systems, with many targeted to the liver, to which natural HDL is targeted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there have been many successful studies using LDL-like nanoparticles for targeted drug delivery to cancer cells. 7,13,[30][31][32][33][34][35] LDL nanoparticles containing lipophilic gadolinium complexes such as Gd-AAZTAC17 are also utilized as MRI probes for tumor cells in vitro and in vivo. 9 Similarly, many HDL nanoparticles have also been developed as drug or gene delivery systems, with many targeted to the liver, to which natural HDL is targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Significant efforts have been devoted to the use of recombinant lipoprotein-like nanoparticles as drug delivery vehicles and diagnostic agents, because most of these particles resemble natural lipoprotein structures and are considered highly biocompatible and safe. [7][8][9][10][11][12] While most LDL-like nanoparticles have been studied as drug delivery or imaging agents for malignant cells expressing LDL receptors, 13 HDL nanoparticles have been used to target hepatocytes and atherosclerotic plaque because the natural function of HDL is to transport cholesterol from the peripheral tissues to the liver through the reverse cholesterol transport pathway. 14 Frias et al prepared HDL-like nanoparticles containing gadolinium-DTPA-conjugated phospholipid and apolipoprotein A-I (apoA-I) proteins or apoA-I mimetic peptides, 18A and 37pA.…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that the uptake of nLDL was time-dependent and concentration-dependent manner. Zhou et al (2010) investigated the uptake extent of sLDL by leukemic cell lines and chronic myeloid leukemia (CML) patient stem/progenitor cells. Compared with Bcr-Abl negative, it showed an increased and preferential uptake of sLDL by Bcr-Abl positive cell lines.…”
Section: Rldlmentioning
confidence: 99%
“…Zhou et al described that the resistance of CML CD34+ and primitive CD34+CD38− cells can be overcome using synthetic low-density lipoprotein (sLDL) particles. 98 sLDL is prepared using a solvent evaporation method involving a mixture consisting of phosphatidylcholine, triolein, cholesterol, and cholesteryl oleate at a molar ratio of 3:2:1:1, respectively. Low-density lipoprotein receptor-specific lipophilic synthetic peptides have been used to target CML cells.…”
Section: Development Of Nanomedicine For Cscs Drug-delivery Systems Fmentioning
confidence: 99%
“…The results indicated that Bcr-Abl-positive cell lines show increased and preferential uptake of sLDL compared with Bcr-Abl negative cells. 98 Nanomedicine has the potential to overcome the known shortcomings of many anticancer agents, including low water-solubility, instability, and nonspecific toxicity. For example, curcumin has been reported to eliminate colorectal CSCs in vitro.…”
Section: Development Of Nanomedicine For Cscs Drug-delivery Systems Fmentioning
confidence: 99%